A Case Study of K-12 School Employee Sexual Misconduct: Lessons Learned from Title IX Policy Implementation, United States, 1984-2014 - Grant, Billie-Jo ([Verlag nicht ermittelbar], 2018)
These data are part of NACJD's Fast Track Release and are distributed as they were received from the data depositor. The files have been zipped by NACJD for release, but not checked or processed except for the removal of direct identifiers. Users should refer to the accompanying readme file for a brief description of the files available with this collection and consult the investigator(s) if further information is needed. This study was designed to examine how districts that experienced an incident of school employee sexual misconduct in 2014 defined, interpreted, and implemented key elements of Title IX before, during, and after an incident. The study used a qualitative case study design with a purposeful sample of five districts recruited from a database of 459 districts who experienced a case of school employee sexual misconduct in 2014. The study was conducted between January 2016 and September 2017. Data collected included: 1) various district documents, 2) 41 interviews with primary actors (school employees and county officials directly involved in responding to the incident), 3) 10 focus groups with 51 secondary actors (school employees who were not directly involved with the incident but who might have been indirectly affected by it), and 4) offender, victim and district characteristics. Documents reviewed included written policies and protocols, training materials and handbooks for staff and students, case documents, and other guiding documents as applicable. In interviews and focus groups, participants were asked to discuss their knowledge of district policies and procedures, to describe the dissemination of and any changes to these policies and procedures, and to provide recommendations for improvement. To protect the confidentiality all district and participant identifying information is confidential and has been removed from any reporting.